Information System for AK1 Management and Job Vacancies (Case Study: Diskominfo Tanjungpinang City) - Magfira, Fortia; Nadia Ayu Putri Priyani; Adinda (STMIK PONTIANAK, 2025)
Digital transformation is a strategic effort to improve the quality of public services in the era of information technology, including in the employment sector. The Tanjungpinang City Manpower Office (Disnaker) faces various challenges in managing job seeker and job vacancy data due to the use of manual systems that are still inefficient. To answer these problems, a web-based Disnaker Admin System was developed using the Laravel framework which aims to facilitate the management of AK1 (yellow card) administration, job seeker data, companies, and job vacancy information. The testing process was carried out using the User Acceptance Testing (UAT) method and involved periodic reviews by the Tanjungpinang City Communication and Informatics Office (Diskominfo) to ensure the suitability of the system with the needs and standards of digital public services. Diskominfo plays an active role as a development partner and supervisor in ensuring that this digital transformation runs according to the direction of local government policy. The implementation results show that this system is able to improve admin work efficiency, accelerate the service process, improve data accuracy, and support more modern and integrated employment data management. Thus, this system provides a real contribution in supporting digital transformation and improving the quality of public services in the employment sector, while strengthening cross-agency collaboration in developing regional information technology solutions.